The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting--Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz--and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Les femmes : caste, classe ou sexe opprimé - Reed, Evelyn (Féminisme et socialisme aux États-Unis. Textes du Parti socialiste des travailleurs, 1979)
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; classe sociale; cours; fem1000; histoire et politique; militance; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Mère de tant d'enfants - Obamsowin, Alanis (1977)
Dans son premier long métrage documentaire, sorti en 1977, Alanis Obomsawin rend hommage à la place centrale des femmes et des mères dans les cultures amérindiennes. Album de témoignages féminins autochtones, le film dépeint ces cultures matriarcales fortes, auxquelles on a tenté d'imposer pendant des siècles des habitudes et coutumes étrangères. Suivant le cycle de la vie des femmes autochtones de la naissance à la vieillesse en passant par l'enfance, la puberté, l'âge adulte et la maturité, il montre comment ces femmes se sont battues pour retrouver un sentiment d'égalité, inculquer la fierté de leur culture à leurs enfants et transmettre leurs histoires aux nouvelles générations.
Keywords: amériques; approches et analyses; cours; documentaire; fem3100; femmes* autochtones; histoire et politique; premier cycle; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children--The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis

From the center: feminist essays on women's art - Lippard, Lucy R. (Dutton paperback original, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis

Un groupe de femmes de Montréal - Un groupe de femmes québécoises. (Manifeste des femmes québécoises, 1971)
Keywords: 1900-1999; 1970-1979; EDI; amériques; approches et analyses; conflit; cours; fem1000; groupes communautaires; histoire et politique; justice sociale; militance; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques

The politics of housework - Mainardi, Patricia; New England Free Press (New England Free Press, 1970)
Keywords: 1900-1999; 1970-1979; amérique du nord; amériques; approches et analyses; care; cours; discipline; féminisme marxiste; histoire et politique; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis